Some Notes on "culture", "Humanism", and the "Humanities" in Modern Chinese Cultural Discourses - Lee, Leo (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1995)
This paper is written in response to the set of questions first raised by Professor Murray Krieger in the planning memo (October 1992) for the First International Conference For Humanistic Discourses [Surfaces IV. 301-311 (1994)]. The first part of this paper attempts to give a broad survey of issues related to humanism and the humanities in 20th-century China. In recontextualizing some of the key terms in Chinese and their cultural translations, the paper also seeks to lay the comparative ground for locating the institutional structures and spaces for cultural criticism in contemporary Chinese culture and society. I believe that only by locating such crucial differences in cultural practice can a meaningful comparative theory be constructed.